THE INFLUENCE OF LINGUISTIC POLITENESS STRATEGIES ON EFFECTIVE CLASSROOM INTERACTION AND STUDENT COMMUNICATION PERFORMANCE IN UNIVERSITAS HARAPAN MEDAN - Emmy Erwina; Lisna Sari Siregar; Bima Prana Chitra; Rayyan Naufal; Muhammad Radit Ardiansyah Putra (Universitas Harapan Medan, 2026)
This study aimed to examine the influence of linguistic politeness strategies on effective classroom interaction and student communication performance at Universitas Harapan Medan. The research employed a mixed-methods approach using a sequential explanatory design, integrating quantitative and qualitative data to provide a comprehensive understanding of the implementation of linguistic politeness strategies in classroom learning. The research process consisted of preliminary observation, needs analysis, instrument development and validation, questionnaire administration, classroom observation, semi-structured interviews, and statistical as well as thematic data analysis. Based on the illustrative simulated dataset, the findings indicate that the implementation of linguistic politeness strategies contributes positively to the development of more effective classroom interaction and improved student communication performance. Lecturers' use of positive politeness strategies promotes a respectful, collaborative, and supportive learning environment, encouraging students to participate actively, express ideas confidently, and engage in meaningful academic discussions. The simulated structural model further suggests that effective classroom interaction functions as a mediating variable that strengthens the relationship between linguistic politeness strategies and student communication performance. These illustrative findings highlight the potential value of integrating pragmatic politeness principles into higher education teaching practices to enhance instructional communication and foster student-centered learning. Future research should employ empirical data from multiple higher education institutions to validate these relationships and improve the generalizability of the findings.